Public financial management reforms: the role of IPSAS in Latin America - Brusca, Isabel; Montesinos, Vicente; Gomez-Villegas, Mauricio (2016)
During the last 30?years, many public administration reforms promoted by New Public Management have been undertaken. These reforms have spread to Latin-American countries and include changes in governmental accounting systems, where the implementation of International Public Sector Accounting Standards (IPSASs) has been a stimulus for modernization. This article aims to clarify the situation of IPSASs implementation in the Latin-American context as well as the stimuli for and effects of their implementation. The analysis shows that there is an emerging international trend to adopt IPSASs in Latin-American countries although at the same time, there are evident obstacles to achieving reform goals. In Colombia, reforms are still underway, and the usefulness of IPSASs to improve decision-making at an organisational level cannot be evaluated. Meanwhile, in Peru, the modernization is more rhetorical than real, and many efforts remain to be made for the effective implementation.
Keywords: Financial administration